CHARACTERIZATION OF Fusarium sp. ASSOCIATED WITH AFRICAN EGGPLANTS (Solanum aethiopicum L. and Solanum macrocarpon L.) IN BURKINA FASO - SOULAMA Aboubacar Siriki; DIANDA Zoéyandé Oumarou; KABORE Boukaré; BATIONO/KANDO Pauline (Journal of Animal and Plant Sciences, 2026)
Eggplants Solanum aethiopicum L. and Solanum macrocarpon L. are packed with essential nutrient constituents necessary for nutritional balance and health maintenance. However, Fusarium infections characterized by leaf yellowing and necrosis, plant wilting and desiccation, as well as fruit rot represent a major constraint to production. This study aims to characterize Fusarium isolates from diseased eggplant plants. This would allow better management of African eggplant production, maintain crop quality, significantly reduce yield losses and above all contribute to ensuring food security. The virulence of 28 Fusarium isolates was assessed by seed inoculation from four S. aethiopicum genotypes and four S. macrocarpon genotypes. Two highly virulent isolates were identified based on the characteristics of mycelium on PDA culture medium, conidia under the microscope and sequences from the ITS region (ITS4 and ITS5). An analysis of variance (ANOVA) was conducted, and mean comparisons were performed via the Newman Keuls test at the 5% threshold. The results showed that all isolates produced symptoms and the most virulent were E38FUS and E41FUS. These two isolates generated respectively high incidence, an average rate of 30.42% in S. aethiopicum and 31% in S. macrocarpon. The same was true for severity with respective indices of 21.13% in S. aethiopicum and 22.63% in S. macrocarpon, further confirming their harmfulness.Fusarium flagelliforme and Fusarium falciforme are the two identified species, representing E38FUS and E41FUS respectively. This study highlights important alternatives, like identification of molecules of interest for biological and chemical treatments, and also varietal screening against Fusarium wilt.
Keywords: African eggplants; Fusarium wilt; pathogenic fungi; molecular identification; F. flagelliforme; F. falciforme.